Persepsi Sosial terhadap Kewarganegaraan Ganda di Indonesia Perspektif Warga Negara dan Non – Warga Negara - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Falakhul Khoir Romadhoni; Nabila Aulya Brilianfineza; Chafia Tawakalluna Anidhita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the social perceptions of dual citizenship in Indonesia from the perspectives of both Indonesian citizens and non-citizens, and compares these views with practices in other countries. Employing a descriptive qualitative approach, the research utilizes in-depth interviews, focus group discussions (FGDs), and surveys to gather data from diverse stakeholders. The findings reveal that in Indonesia, dual citizenship is often perceived as a threat to national identity and unity, primarily due to concerns about divided loyalties. Conversely, non-citizens view dual citizenship as advantageous for accessing various services and opportunities. Comparative analysis with countries such as Germany and Canada shows that dual citizenship policies can be accepted and even considered beneficial for social integration and international relations. Based on these findings, policy recommendations include reforming citizenship laws, adjusting legal and regulatory frameworks, enhancing public awareness, providing support for individuals with dual citizenship, and conducting further research to explore the long-term impacts of dual citizenship.